Job Satisfaction as Mediator Between Organizational Culture and Employee Performance in Government-owned Bank - Raintung, Rahel Debora; Warouw, Yisreel Veronica; Mandagi, Deske W.; Wulyatiningsih, Toetik (Institut Agama Islam Sunan Giri Ponorogo, 2024)
This study investigates the mediating role of employee job satisfaction in the relationship between organizational culture and employee performance within government-owned banks. The research design selected for this study was descriptive, quantitative, and causal. A quantitative survey was conducted to gather data from 110 employees of a government-owned bank in North Sulawesi, Indonesia. Structural Equation Modeling (SEM) was employed as the primary method of data analysis facilitated by SmartPLS software. The results indicate that organizational culture significantly and positively influences job satisfaction, while job satisfaction similarly has a significant and positive impact on employee performance. Furthermore, organizational culture emerges as a significant determinant of employee performance. Additionally, the study reveals that job satisfaction effectively mediates the relationship between organizational culture and employee performance. The practical implications of these results hold significance for organizations, particularly government-owned banks, in enhancing employee performance and organizational effectiveness. By cultivating a culture that aligns with employees' values and fosters engagement, organizations can boost job satisfaction levels, enhancing overall employee performance.